PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP AKTIVITAS SISWA KELAS X DI SMA NEGERI 5 MODEL LUBUKLINGGAU TAHUN PELAJARAN 2018/2019 - Srilisnani M; Ahmad Amin; Yaspin Yolanda (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2019)
This thesis is entitled "The Application of Contextual Teaching And Learning (CTL) Learning Model to the Activities of Class X Students in Lubuklinggau 5 Senior High Schools in Academic Year 2018/2019". The problem in this study is how student learning activities when practicing using CTL learning on the material magnitude and measurement of students of class X MIPA in Lubuklinggau State Senior High School 5 Model 2018/2019. The population in this study were all class X MIPA Lubuklinggau State Senior High School 5 Model 2018/2019 and part of the sample was class X MIPA 4, amounting to 36 students taken randomly. Data collection is done by observation, interviews, questionnaires, and tests. Based on data analysis that 'learning activities at practicum I had a percentage of 76.96% in good category and at practicum II had a percentage of 85.65% very good category for students of class X MIPA 4 in Lubuklinggau Model 5 High School 2018/2019.